A comprehensive review on: Chimeric Antigen Receptor (CAR) T-cell therapy in cancer treatment - Pal, Bikash; Chattaraj, Bornika; Agrawal, Purnima (Journal of Biomedical and Pharmaceutical Research, 2020)
Chimeric antigen receptor T-cells or CAR T-cell therapy is a newly discovered method that has shown great promise for the global patient population to cure cancer. Chimeric antigen receptor T-cells are generally prepared by removing T-cells from the patients’ blood and modifying them using genetic engineering, to express a Chimeric Antigen Receptor on their surface. The studies done so far have shown its major effectiveness against Beta-cell malignancy, ovarian carcinoma, and lymphoblastic leukemia. The therapy can cause Cytokine Release Syndrome, neurotoxicity syndrome, tumor lysis, etc. as its major adverse event. But recent improvements in the therapy has proved that these adverse events can be effectively minimized to a great extent. The future of CAR T-cell therapy is very promising and is expected to fulfil all global regulatory requirements as well as overcome any manufacturing and toxicological obstacles and become available for a large number of populations. This review is based on the overall prospects of CAR T-cell therapy, the major toxicity related problems, and the prospect of this therapy.